Genetic verification of multiple paternity in two free-ranging isolated populations of African wild dogs (Lycaon pictus) - Harper, Cindy Kim (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Sciences))--University of Pretoria, 2006.